2013
DOI: 10.3390/ijerph10083282
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of a Neem Cake Extract in a Broth Model Meat System

Abstract: This work reports on the antimicrobial activity of an ethyl acetate extract of neem (Azadirachta indica) cake (NCE) against bacteria affecting the quality of retail fresh meat in a broth model meat system. NCE (100 µg) was also tested by the agar disc diffusion method. It inhibited the growth of all tested microorganisms. The NCE growth inhibition zone (IZ) ranged 11.33–22.67 mm while the ciprofloxacin (10 µg) IZ ranged from 23.41–32.67 mm. There was no significant difference (p ≤ 0.05) between the antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…which showed promising results (Del Serrone and Nicoletti 2013). From our study, the colony Experiments were repeated thrice for confirmation morphology and hyphae morphology by lactophenol cotton blue test of the fungi were identified to be Aspergillus niger, Rhizopus sps., and Fuserium sps.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…which showed promising results (Del Serrone and Nicoletti 2013). From our study, the colony Experiments were repeated thrice for confirmation morphology and hyphae morphology by lactophenol cotton blue test of the fungi were identified to be Aspergillus niger, Rhizopus sps., and Fuserium sps.…”
Section: Resultsmentioning
confidence: 80%
“…Because of the presence of bitter and toxic triterpenoids, namely nimbin, nimbidin, azadirachtin and salannin, the de-oiled neem cake was not advised as feed stuff (Paul et al 1996). Studies showed that neem predominantly contains salannin by HPLC method (Del Serrone and Nicoletti 2013). Neem oil cake is given as feed, energy source, protein hydrolysate, biochemical source and used for the production of antibiotics, enzymes and mushroom in industries (Sumitra et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The HPTLC analysis showed a very low presence of limonoids and therefore other compounds must be considered responsible of the reported activity [40]. Other activities of neem cake are actually under study, including antibacterial properties that can be used in meat preservation [41].…”
Section: Emergency In Central Italy: the Tiger Mosquitomentioning
confidence: 99%
“…The application of natural antimicrobials instead of the conventional ones might enable the reduction of some potentially toxic conventional food additives and antimicrobials such as nitrites and nitrates [6]. Nowadays, natural antimicrobials such as essential oils of cinnamon and cloves [7] extracts of garlic [8], neem [9] and other spices, oleoresins, fatty acids and their esters or chitosans are widely used in different food products in order to not only establish a safe food preservation process, but also to give the product a new quality and the added value. A search for novel preservation techniques, such as the non-thermal preservation technology [10] together with the modified atmosphere packaging [11] is still going on.…”
Section: Introductionmentioning
confidence: 99%